San Carlos City, Negros Occidental: Prospects and Perspectives as Meetings, Incentives, Conventions, and Exhibitions Destination - Ramirez, Cybill Ann A. (Philippine Social Science Journal, 2021)
Meetings, incentives, conventions, and exhibitions (MICE) tourism is a specialized area of the tourist industry growing in importance due to the growth of business tourism worldwide. In San Carlos City, the MICE industry is not yet fully developed; assessing the city’s potential as a MICE destination is still essential to ascertain if the city has adhered to all the necessary qualifications and has sufficient facilities and services. As a result, using the Five A’s of Tourism, the study assessed the potential of San Carlos City, Negros Occidental as a MICE destination and investigated stakeholders’ perceived demands, difficulties, and opportunities. Using the quota sampling method, data were gathered from the respondents comprising tourism key players and tourists through a researcher-made checklist questionnaire. Descriptive analysis through frequency count and distribution percentage was used to analyze the data. Based on the findings, the city shows potential as a MICE-destination as determined using the Five A’s of tourism. Generally, the study’s findings may provide a basis for a proposed three-year MICE Tourism Development Plan of San Carlos City, Negros Occidental.